Strategi Guru Pendidikan Agama Katolik dalam Implementasi Moderasi Beragama - Yohanes Chandra Kurnia Saputra; Adi Ria Singir Meliyanto (Unit Penelitian dan Pengabdian kepada Masyarakat (UPPM), STP-IPI Malang., 2025)
The multicultural society of Pontianak City demands a strategic role from Catholic Religious Education teachers in implementing the values of religious moderation among students. Schools, as institutions for shaping religious and national character, serve as the most appropriate place to instill these values systematically and sustainably. This study aims to explore the strategies employed by Catholic Religious Education teachers in applying the values of religious moderation through the Merdeka Curriculum. The method used is qualitative research with data collected through in-depth interviews and Focus Group Discussions (FGD) to obtain comprehensive insights. The informants consisted of 20 Catholic Religious Education teachers actively teaching in various schools across Pontianak City. The collected data were analyzed descriptively and qualitatively through the stages of data reduction, data presentation, and conclusion drawing. The findings reveal that the implemented values include tolerance, non-violence, justice, and national commitment. These values are conveyed through narrative approaches, open dialogues, interfaith activities, and consistent character formation. The challenges encountered include external environmental influences that do not always support religious moderation, as well as exclusive mindsets still held by some students. In conclusion, the successful implementation of religious moderation requires cross-sector collaboration and continuous character strengthening within the educational ecosystem. Furthermore, training and curriculum support aligned with these values are necessary to enable teachers to effectively carry out their moderative roles in a pluralistic society.